Vous avez dit post-éditrice ? Quelques éléments d'un parcours personnel - Anne-Marie Robert (JoSTrans: The Journal of Specialised Translation)
The appearance of machine translation in the language industry has given rise to a new language activity: post-editing. This consists in using a combination of various machine translation and computer-aided translation technologies with the aim of improving productivity to cope with ever-increasing translation volumes. The post-editor's task is to go over the work produced by the machine to guarantee that the quality is up to human standard. The context, methodology, professional practices, skills, technological environment and problems posed by this new specialisation are explained in this article in which a practising post-editor shares her experience with the reader by painting her own professional portrait.